Personal Background and Reasons for Choosing a Career in Policing: An Empirical Study of Police Trainees in India (International Journal of Innovative Research in Engineering & Management, 2021)
Policing has traditionally been regarded as a dangerous and  stressful profession. In India, the police–public interaction bears  witness to a persistent, if not rising, distrust, which has a  significant influence on police performance at the front lines,  namely the police station. It is the point of contact between the  criminal justice organization and the community, where  individuals are directly affected by good or terrible justice and  provision of services. Law enforcement officials are responsible  for the fairness and efficacy of the process, and any unjustified  actions alternatively, their actions may erode people's confidence  and tarnish the officer's reputation. Folks, either as topics or also  as artifacts, are at the core of everything. As a result, security must  be neighborhood and neighborhood, with active public  participation. It is required for the reduction of crime, which is  gaining greater attention from governments, civil society, and  even the general public. The current study aimed at investigating  undertaking at the segments and sub in Delhi, India's capital city,  to determine the meaning, acknowledgement, and procedure of  the paradigm change in the police that resulted from the sudden  realization that public cooperation is critical in maintaining  natural cohesion and crime management. A short description of  the foregoing findings and their implications for police recruiting  is offered in accordance with the study of the survey  questionnaires.
Keywords: India; Police; Policing; Public; Trainee